GUILLAIN-BARRÉ SYNDROME AND COVID-19 VACCINATION: A DISCONCERTING ASSOCIATION - SHANMUGAM, SINDHU; JAMES, SELVIN GNANARAJ; SRIRAM, DAMAL KANDADAI; GEORGE, MELVIN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Guillain-Barré syndrome (GBS) is an acute, inflammatory peripheral nerve disorder characterized by rapidly progressive, ascending, symmetrical paresthesia, and motor weakness. Some patients may develop respiratory failure requiring ventilation. The annual incidence of GBS is ~1.7 persons per 100,000 population. We describe the case of a 61-year-old male complaining of headache, one episode of vomiting, giddiness, slight slurring of speech, and inability to close his left eyelid. The patient received intravenous immunoglobulin therapy, with improvement in his symptoms at the time of discharge. In addition, we have also summarized 41 cases of GBS reported on post-COVID-19 vaccination. The intention of this case report is to highlight on the incidence of GBS in individuals who have received COVID-19 vaccine. Moreover, physicians should be aware of GBS in every patient presenting with neurological complaints on OPD.